2022
DOI: 10.1097/shk.0000000000001919
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of IL-38 in Lung Immunity during Pseudomonas Aeruginosa-induced Pneumonia

Abstract: Objective:Interleukin-38 (IL-38), a new type of cytokine, is involved in processes such as tissue repair, inflammatory response, and immune response. However, its function in pneumonia caused by Pseudomonas aeruginosa (P. aeruginosa) is still unclear.Methods:In this study, we detected circulating IL-38 and cytokines such as IL-1β, IL-6, IL-17A, TNF-α, IL-8, and IL-10 in adults affected by early stage pneumonia caused by P. aeruginosa. Collected clinical data of these patients, such as the APACHE II score, leve… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 57 publications
(68 reference statements)
0
3
0
Order By: Relevance
“…IL-38 is a newly discovered cytokine in the IL-1 family and plays an important role in a variety of diseases, including but not limited to CNS diseases. [16][17][18][19][20][21][22][23][24] IL-38 is mainly expressed in the brain, heart, lungs, spleen, thymus, tonsils, and skin, and is less distributed in immune-inactive tissues. 25,26 Moreover, its protein is mainly synthesized and secreted by fibroblast-like synoviocytes, keratinocytes, peripheral blood mononuclear cells, and CD19+ B cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…IL-38 is a newly discovered cytokine in the IL-1 family and plays an important role in a variety of diseases, including but not limited to CNS diseases. [16][17][18][19][20][21][22][23][24] IL-38 is mainly expressed in the brain, heart, lungs, spleen, thymus, tonsils, and skin, and is less distributed in immune-inactive tissues. 25,26 Moreover, its protein is mainly synthesized and secreted by fibroblast-like synoviocytes, keratinocytes, peripheral blood mononuclear cells, and CD19+ B cells.…”
Section: Introductionmentioning
confidence: 99%
“…IL‐38 is a newly discovered cytokine in the IL‐1 family and plays an important role in a variety of diseases, including but not limited to CNS diseases 16–24 . IL‐38 is mainly expressed in the brain, heart, lungs, spleen, thymus, tonsils, and skin, and is less distributed in immune‐inactive tissues 25,26 .…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, with more involved contents, strong subjectivity, and low evaluation efficiency, it cannot provide effective reference for doctors to grasp the optimal treatment opportunity. 3,4 In recent years, studies have shown that microRNA (miRNA) and other biological indexes are closely related to the occurrence and development of pneumonia, which can offer reliable information for pneumonia diagnosis and treatment. [5][6][7] MiR-24 is a miRNA associated with inflammation, lung injury, and pneumonia progression.…”
Section: Introductionmentioning
confidence: 99%